Cadeia de custódia no Acordo de Leniência na Lei de Probidade Administrativa Empresarial - Pires, Vitor Casseb (2025)
This dissertation examines the importance of the chain of custody, as provided in Articles 158-A to 158-F of the Brazilian Code of Criminal Procedure, within the context of leniency agreements established by Federal Law No. 12,846/2013, regulated by Federal Decree No. 11,129/2022, within the scope of the Federal Executive Branch. The research, based on a bibliographic review and an analysis of executed agreements, places the LPAE within the microsystem for the protection of administrative probity, addressing its interrelation with other accountability regimes. The study analyzes the legal nature, requirements, and purposes of leniency agreements, with an emphasis on the acquisition and preservation of evidentiary elements. The study delves into the chain of custody in Criminal Procedural Law, detailing its assumptions, purposes, and the consequences resulting from its violation. Finally, the application of this institute in leniency agreements is examined, highlighting the legal implications of its absence and the impacts on the defense of non-collaborating companies. The study concludes that compliance with the chain of custody is essential to ensure the authenticity and integrity of the evidentiary elements obtained through the leniency agreement, guaranteeing the legitimate and effective exercise of sanctioning competence, in accordance with the principles of due process of law, adversarial proceedings, full defense, the right to lawful evidence, and motivation